1998
DOI: 10.1159/000045187
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Ascorbic Acid and an Aldose Reductase Inhibitor (Tolrestat) in Diabetes: Effect on Urinary Albumin Excretion

Abstract: The important role of ascorbic acid (AA) as an anti-oxidant is particularly relevant in diabetes mellitus where plasma concentrations of AA are reduced. This study was conducted to evaluate the effects of treatment with AA or an aldose reductase inhibitor, tolrestat, on AA metabolism and urinary albumin excretion in diabetes. Blood and urine samples were collected at 0, 3, 6, 9, and 12 months from 20 diabetic subjects who were randomized into two groups to receive either oral AA 500 mg twice daily or placebo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
2
29
1
2
Order By: Relevance
“…When data were reported as subgroups without an overall effect, subgroups were used in the analysis (34,36). In a sensitivity analysis, we included trials with incomplete reporting of BP or BP variance after an assumption of no effect of supplementation on BP (36,(40)(41)(42)(43)(44)(45)(46)(47)(48). See Supplemental Tables 2 and 3 under "Supplemental data" in the online issue for characteristics of these trials and details of our imputation methodology.…”
Section: Discussionmentioning
confidence: 99%
“…When data were reported as subgroups without an overall effect, subgroups were used in the analysis (34,36). In a sensitivity analysis, we included trials with incomplete reporting of BP or BP variance after an assumption of no effect of supplementation on BP (36,(40)(41)(42)(43)(44)(45)(46)(47)(48). See Supplemental Tables 2 and 3 under "Supplemental data" in the online issue for characteristics of these trials and details of our imputation methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies have provided some evidence for a link between oxidant stress and renal damage. In one group of Type I and II diabetic patients, long-term treatment with ascorbate reduced albumin excretion rate [53], and in another similar group α-lipoic acid prevented progression of albuminuria [54]. None of these studies have looked specifically at the role of carotenoids or carotenoid-rich diets.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic animal models and human studies where aldose reductase inhibitors were used to treat or prevent diabetic nephropathy, the outcomes remain controversial (44,50,51,52). We have demonstrated that treatment of STZ-diabetic rats with tolrestat prevents glomerular hyperfiltration, glomerular hypertrophy, and increased microalbuminuria but does not prevent fractional mesangial expansion in the first 12 wk of diabetes (15).…”
Section: The Polyol Pathwaymentioning
confidence: 99%